A lithium ion battery separator with high ionic conductivity and its preparation process
By applying modified MoS2 nanotube @Mg(OH)2 coaxial composite material on the lithium-ion battery separator, the problems of low ionic conductivity, poor mechanical properties and insufficient heat resistance of the separator are solved, and higher conductivity, mechanical strength and heat resistance are achieved, and the safety of the battery is improved.
Patent Information
- Application Number
- CN202211195858.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-29
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2042-09-29
AI Technical Summary
The separators of existing lithium-ion batteries have low ion conductivity, poor mechanical properties, insufficient liquid absorption and liquid retention capabilities, and insufficient heat resistance, resulting in short circuits and spontaneous combustion of batteries at high temperatures.
A coating layer made of modified MoS2 nanotube @Mg(OH)2 coaxial composite material is used to coat both sides of the base film. Through the high aspect ratio of the MoS2 nanotube and the flame retardant properties of Mg(OH)2, a 3-dimensional mesh structure is formed to enhance the mechanical strength and thermal shrinkage performance of the diaphragm.
It significantly improves the ionic conductivity, mechanical strength, liquid absorption and heat resistance of the lithium-ion battery separator, reduces the risk of short circuit and spontaneous combustion of the battery at high temperatures, and improves the safety of the battery.
Smart Images

Figure BDA0003870580240000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery separator with high ion conductivity and a preparation process thereof. Background Art
[0002] Polyolefin separators are currently the most widely used lithium battery separators. However, the existing polyolefin separators on the market also have some disadvantages: ① Low ionic conductivity makes the internal resistance of the battery large, which is not conducive to the charging and discharging of lithium-ion batteries at high rates; ② Low mechanical strength and poor puncture resistance. They are easily punctured, causing short circuits between the positive and negative electrodes of the battery and thermal runaway; ③ The melting point of polyolefin materials is very low. When the battery has thermal runaway, the separator is prone to rupture, resulting in more severe thermal runaway, which can cause the battery to burn or even explode; ④ Low specific surface area and poor liquid absorption and retention capabilities. The current main solution to the problems of low ionic conductivity, poor mechanical properties, and poor liquid absorption and retention of polyolefin separators is to apply a ceramic coating on one or both sides of the polyolefin separator; and to the problem of poor heat resistance of polyolefin separators, by applying a high-temperature resistant ceramic coating on the surface of the polyolefin separator, the closure of the separator can be delayed to 150°C, but the closure temperature of 150°C cannot completely prevent the short circuit of lithium batteries at high temperatures and the spontaneous combustion caused by it. Therefore, it is necessary to further improve the heat resistance of the separator, reduce the risk of membrane rupture, and thus improve the safety of the battery. Therefore, the development of lithium-ion battery separators with high flame retardancy, high electrolyte wettability, and high ionic conductivity has become a common goal pursued by the industry. Summary of the invention
[0003] The object of the present invention is to provide a lithium ion battery separator with high ionic conductivity and a preparation process thereof, so as to solve the problems raised in the above background technology.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: A lithium ion battery separator with high ionic conductivity has the following characteristics: The lithium ion battery separator with high ionic conductivity is composed of a base film and a coating layer coated on both sides of the base film;
[0005] The coating layer comprises the following components: 9-19% modified MoS2 nanotube@Mg(OH)2 coaxial composite material, 0.2-0.6% dispersant, 0.4-0.7% thickener, 0.5-1% adhesive, 0.05-0.2% wetting agent, and the balance is ultrapure water.
[0006] Furthermore, the dispersant is a hydrolyzed polymaleic anhydride (HPMA) dispersant; and the thickener is a sodium hydroxymethylcellulose thickener.
[0007] Furthermore, the adhesive is a COPNA resin adhesive; and the wetting agent is a silanol nonionic surfactant.
[0008] Furthermore, the modified MoS2 nanotube@Mg(OH)2 coaxial composite material is prepared by reacting MnCO3 nanotubes prepared from MnCO3 nanowires with magnesium sulfate and ammonia water, grafting methyl acrylate on the surface and then calcining;
[0009] Among them, MnCO3 nanowires are prepared by potassium permanganate and manganese chloride under the catalytic oxidation reaction of hexadecyltrimethylammonium bromide and hydrogen peroxide.
[0010] A process for preparing a lithium-ion battery separator with high ionic conductivity comprises the following steps:
[0011] S1. Preparation of modified MoS2 nanotubes@Mg(OH)2 coaxial composites;
[0012] S11. Potassium permanganate and manganese chloride were dissolved in deionized water, and ultrasonically treated for 20-30 minutes. Hexadecyltrimethylammonium bromide and hydrogen peroxide were added, and after mixing, lithium carbonate was added. The mixture was stirred for 35-45 minutes, and the temperature was raised to 180°C. The reaction was carried out in a sealed state at high temperature for 18-24 hours. After the reaction was completed, the heating was stopped, and the mixture was cooled to room temperature and filtered. The mixture was washed alternately with anhydrous ethanol and deionized water for 5-8 times, and vacuum dried to obtain MnCO3 nanowires.
[0013] S12. The MnCO3 nanowires prepared in step S11 are dispersed in deionized water, dispersed and mixed for 2-3 hours, and then Na2MoO4·2H2O and L-cysteine are added, and the dispersion treatment is continued for 1-2 hours, and the temperature is raised to 230-260°C, and the reaction is carried out in a high pressure sealed state for 24-30 hours. After the reaction is completed, the heating is stopped, and the mixture is cooled to room temperature and filtered, and washed alternately with anhydrous ethanol and deionized water for 5-8 times, vacuum dried, and soaked in hydrochloric acid for 36-48 hours, filtered, and the precipitate is washed to neutral, and vacuum dried to obtain MoS2 nanotubes;
[0014] MoS2 nanotubes have an extremely high aspect ratio, good thermal conductivity and high temperature resistance. In the coating slurry, the modified MoS2 nanotube@Mg(OH)2 coaxial composite material using MoS2 nanotubes as the matrix can utilize the high aspect ratio of MoS2 nanotubes to cross-link in the coating to form a three-dimensional network structure, thereby improving the tensile resistance and enhancing its puncture resistance, hindering the growth and puncture of lithium dendrites, and improving the safety performance of the battery separator.
[0015] S13. Dissolve magnesium sulfate in ultrapure water to prepare a magnesium sulfate solution, add the MoS2 nanotubes prepared in step S12, stir and disperse for 40-60 minutes, perform ultrasonic dispersion treatment for 3-4 hours, heat to 65-75°C, add ammonia water dropwise, control the pH value of the reaction end point to 8-10, filter and use anhydrous ethanol and ultrapure water to wash the precipitate alternately until it is neutral, and vacuum dry to obtain a MoS2 nanotube@Mg(OH)2 coaxial composite material;
[0016] The flame retardant effect of Mg(OH)2 comes from the carbonized layer formed when the crystal water of Mg(OH)2 decomposes and absorbs heat. When the temperature rises to the decomposition temperature, Mg(OH)2 decomposes to release water vapor, absorbs latent heat, dilutes the concentration of oxygen and combustible gas near the surface of the burning object, and makes it difficult for the surface to burn; the carbonized layer formed on the surface prevents the entry of oxygen and heat, and the magnesium oxide generated by its decomposition is also a good refractory material with good high temperature resistance and thermal conductivity, which can improve the material's ability to resist open flames.
[0017] S14. Dissolve γ-aminopropyltriethoxysilane in deionized water to prepare a γ-aminopropyltriethoxysilane aqueous solution, add MoS2 nanotubes @Mg(OH)2 coaxial composite material, heat to 70-80°C, ultrasonically disperse and react for 12-18 hours, filter, collect the filtered MoS2 nanotubes @Mg(OH)2 coaxial composite material, disperse it in ultrapure water, add methyl acrylate dropwise, heat to 80-90°C, add potassium persulfate, ultrasonically react for 12-18 hours, filter, protect under argon atmosphere, heat to 270-300°C, calcine for 1-2 hours, and cool to room temperature to obtain a modified MoS2 nanotubes @Mg(OH)2 coaxial composite material;
[0018] The present invention also further grafts methyl acrylate on the surface of the MoS2 nanotube@Mg(OH)2 coaxial composite material. First, the present invention uses γ-aminopropyltriethoxysilane to graft amino groups on the surface of the MoS2 nanotube@Mg(OH)2 coaxial composite material, and uses amino groups with high reactivity to graft methacrylic acid on the surface of the coaxial composite material with the participation of potassium persulfate; then the present invention heats it, strictly limits the heating temperature under an argon atmosphere, and carbonizes the methacrylic acid on its surface at the decomposition temperature of materials such as magnesium hydroxide, generates carbon materials on the surface, enhances the binding properties of the remaining COPNA resins, and enhances the stability of the coating.
[0019] S2. The modified MoS2 nanotube @Mg(OH)2 coaxial composite material and dispersant are added to ultrapure water, premixed for 10-30 minutes, a thickener is added, and the dispersion is continued for 20-60 minutes. A binder is added and the mixing is continued for 30-50 minutes. A wetting agent is added and stirred for 20-40 minutes. The modified MoS2 nanotube @Mg(OH)2 coating slurry is obtained by filtering and removing iron;
[0020] S3. The modified MoS2 nanotube@Mg(OH)2 coating slurry is coated on both sides of the base film, baked at 70-80°C for 1-3 minutes, and then rolled up to obtain a lithium-ion battery separator with high ionic conductivity.
[0021] Furthermore, in terms of weight, in step S11, the mass ratio of potassium permanganate, manganese chloride and deionized water is (0.08-0.12):(0.25-0.3):(43-48).
[0022] Furthermore, the mass ratio of deionized water, hexadecyltrimethylammonium bromide, hydrogen peroxide and lithium carbonate is (43-48): (0.12-0.15): (0.5-0.6): (0.09-0.12).
[0023] Furthermore, in terms of weight, in step S12, the mass ratio of MnCO3 nanowires, deionized water, Na2MoO4·2H2O and L-cysteine is (0.4-0.5):(75-80):(0.62-0.68):(2.5-2.8).
[0024] Furthermore, in step S13, the concentration of the magnesium sulfate solution is 1.8-2.1 mol / L; the concentration of the ammonia water is 2-2.5 mol / L.
[0025] Furthermore, in terms of weight, in step S14, the mass ratio of γ-aminopropyltriethoxysilane, MoS2 nanotube@Mg(OH)2 coaxial composite material, methyl acrylate, and potassium persulfate is (3.6-4.5):(1.2-1.56):(0.2-0.3):(0.02-0.03).
[0026] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention first prepares MoS2 nanotubes, which have good high temperature resistance and thermal conductivity, and the nanotubes have a hollow structure, which can effectively improve the conductivity of lithium ions, increase the surface area of the diaphragm, and enhance the liquid absorption and retention capacity; on this basis, the present invention further combines MoS2 nanotubes with Mg(OH)2 with flame retardant function to prepare MoS2 nanotube@Mg(OH)2 coaxial composite materials with extremely high aspect ratio, which can form a mutually cross-linked network structure in the coating, thereby greatly improving the mechanical strength and thermal shrinkage performance of the diaphragm. In addition, the present invention also grafts methyl methacrylate on its surface, and utilizes high-temperature carbonization to graft carbon materials on its surface, thereby enhancing its bonding ability with COPNA resin binders and improving the performance of the diaphragm. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] In the comparative example of the present invention, the thickener is sodium hydroxymethyl cellulose; the dispersant is hydrolyzed maleic anhydride HPMA sold by Shandong Wanhua Tianhe New Materials Co., Ltd.; the wetting agent is silanetriol trehalose ether; the polyolefin separator is PE film;
[0029] The adhesive is a B-stage COPNA resin, which is prepared according to the disclosed content of the document "Jiang Wenjing, Chen Xiaohong, Song Huaihe, Yue Yongde, Tang Feng, Wang Jin, Yao Xi. Synthesis and performance study of bamboo tar-based COPNA resin [J]. Carbon Technology, 2016, 35(04): 41-44. DOI: 10.14078 / j.cnki.1001-3741.2016.04.011."
[0030] Example 1.
[0031] A process for preparing a lithium-ion battery separator with high ionic conductivity, characterized in that it comprises the following steps:
[0032] S1. Preparation of modified MoS2 nanotubes@Mg(OH)2 coaxial composites;
[0033] S11. 0.088g potassium permanganate and 0.267g manganese chloride were dissolved in 45ml deionized water, ultrasonically treated for 20min, 0.13g hexadecyltrimethylammonium bromide and 0.52ml 30% hydrogen peroxide were added, mixed evenly, 0.095g lithium carbonate was added, stirred and reacted for 35min, the mixed solution was transferred to a high-pressure reactor lined with polytetrafluoroethylene, and then placed in an oven and kept at 180°C for 20h. After the reaction was completed, the heating was stopped, and the mixture was cooled to room temperature and filtered, and washed alternately with anhydrous ethanol and deionized water for 5 times, and vacuum dried to obtain MnCO3 nanowires;
[0034] S12. Disperse 0.4138 g of the MnCO3 nanowires obtained in step S11 into 78 ml of deionized water, stir and mix for 40 min, and then ultrasonically disperse for 2 h. Add 0.6533 g of Na2MoO4·2H2O and 2.5080 g of L-cysteine, continue stirring for 20 min, and then ultrasonically disperse for 40 min. Heat to 230°C and react under high pressure for 26 h. After the reaction is completed, stop heating, cool to room temperature, filter, and wash alternately with anhydrous ethanol and deionized water for 5 times, vacuum dry, soak in 2.0 mol / L hydrochloric acid for 40 h, filter, wash the precipitate to neutrality, and vacuum dry at 80°C for 12 h to obtain MoS2 nanotubes.
[0035] S13. Dissolve magnesium sulfate in 200 ml ultrapure water to prepare a magnesium sulfate solution with a concentration of 1.88 mol / L, add 1.59 g of MoS2 nanotubes prepared in step S12, stir and disperse for 60 min, perform ultrasonic dispersion for 3 h, heat to 70°C, drip ammonia water with a concentration of 2 mol / L at a drip rate of 44 ml / min, control the pH value of the reaction endpoint to 8-10, filter and wash the precipitate with anhydrous ethanol and ultrapure water alternately until it is neutral, and dry it at 80°C in vacuum for 12 h to obtain a MoS2 nanotube@Mg(OH)2 coaxial composite material;
[0036] S14. Dissolve 3.805g of γ-aminopropyltriethoxysilane in 45ml of deionized water to prepare a γ-aminopropyltriethoxysilane aqueous solution, add 1.59g of MoS2 nanotubes @Mg(OH)2 coaxial composite material, heat to 75°C, ultrasonically disperse and react for 16h, filter, collect the filtered MoS2 nanotubes @Mg(OH)2 coaxial composite material, disperse it in ultrapure water, drop 0.252g of methyl acrylate, heat to 85°C, add 0.02g of potassium persulfate, ultrasonically react for 12h, filter, protect under argon atmosphere, heat to 270°C, calcine for 1h, and cool to room temperature to obtain a modified MoS2 nanotubes @Mg(OH)2 coaxial composite material;
[0037] S2. 9 g of modified MoS2 nanotube @Mg(OH)2 coaxial composite material and 0.2 g of dispersant were added to 89.23 g of ultrapure water, premixed at 300 rpm for 30 min, 0.66 g of thickener was added, and the mixture was dispersed at 400 rpm for 45 min. 0.79 g of binder was added, and the mixture was mixed at 420 rpm for 40 min. 0.12 g of wetting agent was added, and the mixture was stirred at 550 rpm for 35 min. The modified MoS2 nanotube @Mg(OH)2 coating slurry was obtained.
[0038] S3. The modified MoS2 nanotube@Mg(OH)2 coating slurry was coated on both sides of a polyolefin separator with a thickness of 9 μm. The coating thickness on one side was 3 μm. After baking at 70°C for 3 min, the membrane was rolled up to obtain a lithium-ion battery separator with high ionic conductivity.
[0039] Example 2.
[0040] Compared with Example 1, this example increases the amount of modified MoS2 nanotube@Mg(OH)2 coaxial composite material added in step S2;
[0041] A process for preparing a lithium-ion battery separator with high ionic conductivity, characterized in that it comprises the following steps:
[0042] S1. Preparation of modified MoS2 nanotubes@Mg(OH)2 coaxial composites;
[0043] S11. 0.088g potassium permanganate and 0.267g manganese chloride were dissolved in 45ml deionized water, ultrasonically treated for 20min, 0.13g hexadecyltrimethylammonium bromide and 0.52ml 30% hydrogen peroxide were added, mixed evenly, 0.095g lithium carbonate was added, stirred and reacted for 35min, the mixed solution was transferred to a high-pressure reactor lined with polytetrafluoroethylene, and then placed in an oven and kept at 180°C for 20h. After the reaction was completed, the heating was stopped, and the mixture was cooled to room temperature and filtered, and washed alternately with anhydrous ethanol and deionized water for 5 times, and vacuum dried to obtain MnCO3 nanowires;
[0044] S12. Disperse 0.4138 g of the MnCO3 nanowires obtained in step S11 into 78 ml of deionized water, stir and mix for 40 min, and then ultrasonically disperse for 2 h. Add 0.6533 g of Na2MoO4·2H2O and 2.5080 g of L-cysteine, continue stirring for 20 min, and then ultrasonically disperse for 40 min. Heat to 230°C and react under high pressure for 26 h. After the reaction is completed, stop heating, cool to room temperature, filter, and wash alternately with anhydrous ethanol and deionized water for 5 times, vacuum dry, soak in 2.0 mol / L hydrochloric acid for 40 h, filter, wash the precipitate to neutrality, and vacuum dry at 80°C for 12 h to obtain MoS2 nanotubes.
[0045] S13. Dissolve magnesium sulfate in 200 ml ultrapure water to prepare a magnesium sulfate solution with a concentration of 1.88 mol / L, add 1.59 g of MoS2 nanotubes prepared in step S12, stir and disperse for 60 min, perform ultrasonic dispersion for 3 h, heat to 70°C, drip ammonia water with a concentration of 2 mol / L at a drip rate of 44 ml / min, control the pH value of the reaction endpoint to 8-10, filter and wash the precipitate with anhydrous ethanol and ultrapure water alternately until it is neutral, and dry it at 80°C in vacuum for 12 h to obtain a MoS2 nanotube@Mg(OH)2 coaxial composite material;
[0046] S14. Dissolve 3.805g of γ-aminopropyltriethoxysilane in 45ml of deionized water to prepare a γ-aminopropyltriethoxysilane aqueous solution, add 1.59g of MoS2 nanotubes @Mg(OH)2 coaxial composite material, heat to 75°C, ultrasonically disperse and react for 16h, filter, collect the filtered MoS2 nanotubes @Mg(OH)2 coaxial composite material, disperse it in ultrapure water, drop 0.252g of methyl acrylate, heat to 85°C, add 0.02g of potassium persulfate, ultrasonically react for 12h, filter, protect under argon atmosphere, heat to 270°C, calcine for 1h, and cool to room temperature to obtain a modified MoS2 nanotubes @Mg(OH)2 coaxial composite material;
[0047] S2. 14 g of modified MoS2 nanotube @Mg(OH)2 coaxial composite material and 0.2 g of dispersant were added to 84.23 g of ultrapure water, premixed at 300 rpm for 30 min, 0.66 g of thickener was added, and the mixture was dispersed at 400 rpm for 45 min. 0.79 g of binder was added, and the mixture was mixed at 420 rpm for 40 min. 0.12 g of wetting agent was added, and the mixture was stirred at 550 rpm for 35 min. The modified MoS2 nanotube @Mg(OH)2 coating slurry was obtained.
[0048] S3. The modified MoS2 nanotube@Mg(OH)2 coating slurry was coated on both sides of a polyolefin separator with a thickness of 9 μm. The coating thickness on one side was 3 μm. After baking at 70°C for 3 min, the membrane was rolled up to obtain a lithium-ion battery separator with high ionic conductivity.
[0049] Example 3.
[0050] Compared with Example 1, this example increases the amount of modified MoS2 nanotube@Mg(OH)2 coaxial composite material added in step S2;
[0051] A process for preparing a lithium-ion battery separator with high ionic conductivity, characterized in that it comprises the following steps:
[0052] S1. Preparation of modified MoS2 nanotubes@Mg(OH)2 coaxial composites;
[0053] S11. 0.088g potassium permanganate and 0.267g manganese chloride were dissolved in 45ml deionized water, ultrasonically treated for 20min, 0.13g hexadecyltrimethylammonium bromide and 0.52ml 30% hydrogen peroxide were added, mixed evenly, 0.095g lithium carbonate was added, stirred and reacted for 35min, the mixed solution was transferred to a high-pressure reactor lined with polytetrafluoroethylene, and then placed in an oven and kept at 180°C for 20h. After the reaction was completed, the heating was stopped, and the mixture was cooled to room temperature and filtered, and washed alternately with anhydrous ethanol and deionized water for 5 times, and vacuum dried to obtain MnCO3 nanowires;
[0054] S12. Disperse 0.4138 g of the MnCO3 nanowires obtained in step S11 into 78 ml of deionized water, stir and mix for 40 min, and then ultrasonically disperse for 2 h. Add 0.6533 g of Na2MoO4·2H2O and 2.5080 g of L-cysteine, continue stirring for 20 min, and then ultrasonically disperse for 40 min. Heat to 230°C and react under high pressure for 26 h. After the reaction is completed, stop heating, cool to room temperature, filter, and wash alternately with anhydrous ethanol and deionized water for 5 times, vacuum dry, soak in 2.0 mol / L hydrochloric acid for 40 h, filter, wash the precipitate to neutrality, and vacuum dry at 80°C for 12 h to obtain MoS2 nanotubes.
[0055] S13. Dissolve magnesium sulfate in 200 ml ultrapure water to prepare a magnesium sulfate solution with a concentration of 1.88 mol / L, add 1.59 g of MoS2 nanotubes prepared in step S12, stir and disperse for 60 min, perform ultrasonic dispersion for 3 h, heat to 70°C, drip ammonia water with a concentration of 2 mol / L at a drip rate of 44 ml / min, control the pH value of the reaction endpoint to 8-10, filter and wash the precipitate with anhydrous ethanol and ultrapure water alternately until it is neutral, and dry it at 80°C in vacuum for 12 h to obtain a MoS2 nanotube@Mg(OH)2 coaxial composite material;
[0056] S14. Dissolve 3.805g of γ-aminopropyltriethoxysilane in 45ml of deionized water to prepare a γ-aminopropyltriethoxysilane aqueous solution, add 1.59g of MoS2 nanotubes @Mg(OH)2 coaxial composite material, heat to 75°C, ultrasonically disperse and react for 16h, filter, collect the filtered MoS2 nanotubes @Mg(OH)2 coaxial composite material, disperse it in ultrapure water, drop 0.252g of methyl acrylate, heat to 85°C, add 0.02g of potassium persulfate, ultrasonically react for 12h, filter, protect under argon atmosphere, heat to 270°C, calcine for 1h, and cool to room temperature to obtain a modified MoS2 nanotubes @Mg(OH)2 coaxial composite material;
[0057] S2. 19 g of modified MoS2 nanotube @Mg(OH)2 coaxial composite material and 0.2 g of dispersant were added to 79.23 g of ultrapure water, premixed at 300 rpm for 30 min, 0.66 g of thickener was added, and the mixture was dispersed at 400 rpm for 45 min. 0.79 g of binder was added, and the mixture was mixed at 420 rpm for 40 min. 0.12 g of wetting agent was added, and the mixture was stirred at 550 rpm for 35 min. The modified MoS2 nanotube @Mg(OH)2 coating slurry was obtained.
[0058] S3. The modified MoS2 nanotube@Mg(OH)2 coating slurry was coated on both sides of a polyolefin separator with a thickness of 9 μm. The coating thickness on one side was 3 μm. After baking at 70°C for 3 min, the membrane was rolled up to obtain a lithium-ion battery separator with high ionic conductivity.
[0059] Comparative Example 1.
[0060] This comparative example only uses the polyolefin separator coated with a coating as the lithium ion battery separator.
[0061] Testing: Examples 1-3 and Comparative Example 1 were tested according to the testing standard of GB / T 36363-2018, and their air permeability was tested by a Gurley air permeability tester, and their peel strength and needle puncture strength were tested by a universal testing machine;
[0062] The liquid absorption rate test method is as follows: prepare the battery separator into a 50mm×50mm sample, take it out and weigh it after drying for 24 hours, record it as M; immerse it in a beaker filled with electrolyte, soak it for 10 minutes, take it out and weigh it immediately, record it as M1. The liquid absorption rate is calculated as mass fraction, that is, liquid absorption rate = (M1-M) / M;
[0063] The liquid retention rate test method is as follows: prepare the battery separator into a 50mm×50mm sample, take it out and weigh it after drying for 24 hours, record it as M; immerse it in a beaker filled with electrolyte, soak it for 10 minutes, take it out, suspend it in the air for 3 minutes to remove part of the electrolyte, and then weigh it, record it as M2. The liquid absorption rate is calculated as mass fraction, that is, liquid absorption rate = (M2-M) / M;
[0064] See the table below for specific data;
[0065]
[0066] From the above, we can see that:
[0067] By comparing Examples 1-3 and Comparative Example 1, it can be seen that the modification of MoS2 nanotubes @Mg(OH)2 greatly improves the mechanical strength (needle puncture strength) of the diaphragm; by comparing Examples 1-3 and Comparative Example 1, it can be seen that when the mass ratio of MoS2 nanotubes @Mg(OH)2 in the slurry is gradually increased from 9% to 19%, the liquid absorption rate and liquid retention rate of the corresponding composite diaphragm are getting better and better, that is, the electrolyte wettability is getting better and better, and both are much higher than the pure polyolefin diaphragm without coating, which confirms that the modification of MoS2 nanotubes @Mg(OH)2 can effectively improve the electrolyte wettability ... When the mass ratio of MoS2 nanotubes@Mg(OH)2 gradually increases from 9% to 19%, the ionic conductivity of the corresponding composite membrane becomes higher and higher, and is much higher than that of the pure polyolefin membrane without coating, which confirms that the modification of MoS2 nanotubes@Mg(OH)2 can effectively improve the ionic conductivity of the membrane; By comparing Examples 1-3 and Comparative Example 1, it can be seen that when the mass ratio of MoS2 nanotubes@Mg(OH)2 in the slurry gradually increases from 9% to 19%, the thermal shrinkage performance of the corresponding composite membrane becomes better and better, and is much better than that of the pure polyolefin membrane without coating, which confirms the effectiveness of MoS2 nanotubes@Mg(OH)2 in improving heat resistance.
[0068] By comparing Examples 1-3 and Comparative Example 1, it can be seen that when the mass ratio of MoS2 nanotubes@Mg(OH)2 in the slurry gradually increases from 9% to 14%, the air permeability of the corresponding composite membrane deteriorates. When the mass ratio of MoS2 nanotubes@Mg(OH)2 is further increased to 19%, the air permeability of the corresponding composite membrane seriously deteriorates, and is worse than that of the pure polyolefin membrane without coating. Therefore, in order to balance the various performances of the composite membrane, the addition amount of MoS2 nanotubes@Mg(OH)2 should be moderate, and the more the better. By comparing Examples 1-3 and Comparative Example 1, it can be seen that the oxygen index of the composite membrane modified with MoS2 nanotubes@Mg(OH)2 is much greater than the oxygen index of the pure polyolefin membrane without coating, which confirms that MoS2 nanotubes@Mg(OH)2 can effectively improve the flame retardant properties of the membrane.
[0069] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A process for preparing a lithium-ion battery separator with high ionic conductivity, characterized in that: The following steps are involved: S1. Preparation of modified MoS2 nanotube@Mg(OH)2 coaxial composites; S11. Potassium permanganate and manganese chloride are dissolved in deionized water, ultrasonically treated for 20-30 minutes, hexadecyltrimethylammonium bromide and hydrogen peroxide are added, mixed evenly, lithium carbonate is added, stirred for reaction for 35-45 minutes, heated to 180°C, and reacted in a sealed state at high temperature for 18-24 hours. After the reaction is completed, heating is stopped, the mixture is cooled to room temperature, filtered, and washed alternately with anhydrous ethanol and deionized water for 5-8 times, and vacuum dried to obtain MnCO3 nanowires; S12. The MnCO3 nanowires prepared in step S11 are dispersed in deionized water, dispersed and mixed for 2-3 hours, and then Na2MoO4•2H2O and L-cysteine are added, and the dispersion treatment is continued for 1-2 hours, and the temperature is raised to 230-260°C, and the reaction is carried out in a high pressure sealed state for 24-30 hours. After the reaction is completed, the heating is stopped, and the mixture is cooled to room temperature and filtered, and washed alternately with anhydrous ethanol and deionized water for 5-8 times, vacuum dried, and soaked in hydrochloric acid for 36-48 hours, filtered, and the precipitate is washed to neutral, and vacuum dried to obtain MoS2 nanotubes; S13. Dissolve magnesium sulfate in ultrapure water to prepare a magnesium sulfate solution, add the MoS2 nanotubes prepared in step S12, stir and disperse for 40-60 minutes, perform ultrasonic dispersion treatment for 3-4 hours, heat to 65-75°C, drop ammonia water, control the pH value of the reaction end point to 8-10, filter and wash the precipitate with anhydrous ethanol and ultrapure water alternately until it is neutral, and vacuum dry to obtain a MoS2 nanotube@Mg(OH)2 coaxial composite material; S14. Dissolve γ-aminopropyltriethoxysilane in deionized water to prepare a γ-aminopropyltriethoxysilane aqueous solution, add MoS2 nanotubes @Mg(OH)2 coaxial composite material, heat to 70-80°C, ultrasonically disperse and react for 12-18 hours, filter, collect the filtered MoS2 nanotubes @Mg(OH)2 coaxial composite material, disperse it in ultrapure water, add methyl acrylate dropwise, heat to 80-90°C, add potassium persulfate, ultrasonically react for 12-18 hours, filter, protect under argon atmosphere, heat to 270-300°C, calcine for 1-2 hours, and cool to room temperature to obtain a modified MoS2 nanotubes @Mg(OH)2 coaxial composite material; S2. The modified MoS2 nanotube @Mg(OH)2 coaxial composite material and dispersant are added to ultrapure water, premixed for 10-30 minutes, a thickener is added, and the mixture is dispersed for 20-60 minutes. A binder is added and mixed for 30-50 minutes. A wetting agent is added and stirred for 20-40 minutes. The modified MoS2 nanotube @Mg(OH)2 coating slurry is obtained by filtering and removing iron. S3. The modified MoS2 nanotube@Mg(OH)2 coating slurry is coated on both sides of the base film, baked at 70-80°C for 1-3 minutes, and then rolled up to obtain a lithium-ion battery separator with high ionic conductivity.
2. The process for preparing a lithium-ion battery separator with high ionic conductivity according to claim 1, characterized in that: Measured by mass percentage, the modified MoS2 nanotube@Mg(OH)2 coating slurry includes the following components: 9-19% modified MoS2 nanotube@Mg(OH)2 coaxial composite material, 0.2-0.6% dispersant, 0.4-0.7% thickener, 0.5-1% binder, 0.05-0.2% wetting agent, and the balance is ultrapure water.
3. The process for preparing a lithium ion battery separator with high ionic conductivity according to claim 1, characterized in that: The dispersant is a hydrolyzed polymaleic anhydride (HPMA) dispersant; and the thickener is a sodium hydroxymethylcellulose thickener.
4. The process for preparing a lithium ion battery separator with high ionic conductivity according to claim 1, characterized in that: The binder is a COPNA resin binder; the wetting agent is a silanol nonionic surfactant.
5. The process for preparing a lithium ion battery separator with high ionic conductivity according to claim 1, characterized in that: In terms of weight, in step S11, the mass ratio of potassium permanganate, manganese chloride and deionized water is (0.08-0.12): (0.25-0.3): (43-48).
6. The process for preparing a lithium ion battery separator with high ionic conductivity according to claim 1, characterized in that: In step S11, the mass ratio of deionized water, hexadecyltrimethylammonium bromide, hydrogen peroxide and lithium carbonate is (43-48): (0.12-0.15): (0.5-0.6): (0.09-0.12).
7. The process for preparing a lithium-ion battery separator with high ionic conductivity according to claim 1, characterized in that: In terms of weight, in step S12, the mass ratios of MnCO3 nanowires, deionized water, Na2MoO4•2H2O and L-cysteine are (0.4-0.5): (75-80): (0.62-0.68): (2.5-2.8).
8. The process for preparing a lithium-ion battery separator with high ionic conductivity according to claim 1, characterized in that: In step S13, the concentration of the magnesium sulfate solution is 1.8-2.1 mol / L; the concentration of the ammonia water is 2-2.5 mol / L.
9. The process for preparing a lithium ion battery separator with high ionic conductivity according to claim 1, characterized in that: In terms of weight, in step S14, the mass ratio of γ-aminopropyltriethoxysilane, MoS2 nanotube@Mg(OH)2 coaxial composite material, methyl acrylate, and potassium persulfate is (3.6-4.5): (1.2-1.56): (0.2-0.3): (0.02-0.03).
Citation Information
Patent Citations
Diaphragm and electrochemical device
CN112467309A
Lithium ion battery diaphragm with high flame retardance and high mechanical strength and preparation method thereof
CN114188665A